Philanthropy and social capital in Mexico. Issue 3 (2nd July 2014) - Layton, Michael D.; Moreno, Alejandro
<x xml:space="preserve">Abstract</x> The aim of this paper is to examine the factors underlying philanthropic behavior in Mexico. In particular, we analyze the influence of social capital on two types of behavior: giving and volunteering. This research is based upon groundbreaking national public opinion surveys conducted in 2005 and 2008, the first of their kind in Mexico to focus on donations and volunteerism. We find that membership in associations (an important component of social capital) is strongly and positively associated with secular giving and volunteering. We also tested the role of three other aspects of social capital: participation in informal personal networks, a belief in the norm of reciprocity, and interpersonal trust, and our findings show that the former two have a consistently significant effect on our dependent variables but interpersonal trust does not. We discuss the implications of this for a society where trust in others is comparatively low. Differences between Mexico and the USA, for example, highlight the importance of context in philanthropic behavior. Mexicans' religiosity also stands out as an important variable, particularly when it comes to understanding religious forms of giving and volunteering in the country. The practical significance of our findings for the promotion of philanthropy is that Mexican nonprofits must compensate for being in a low‐trust culture by encouraging membership and a sense of group belonging. Copyright © 2014 John Wiley & Sons, Ltd.